TINJAUAN YURIDIS PERJANJIAN KONTRAK KERJA KARYAWAN TEMPAT HIBURAN MALAM DI KOTA SAMARINDA PADA MASA PANDEMI COVID-19 - Saputro, Rahmat Andi (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACT The presence of the Covid-19 virus has had a very broad impact. In particular, the night entertainment industry has also been affected by the Covid-19 pandemic in Samarinda City. With this pandemic, it will also affect the work contract agreement at night entertainment venues, especially regarding the rights and obligations between Muse Entertaimant and employees.The problems raised in this study are the work contract agreements for night entertainment employees in Samarinda City during the Covid-19 pandemic and forms of legal protection for the rights of night entertainment employees in Samarinda City during the Covid-19 pandemic.The type of research used is normative juridical research, the problem approach used in writing this thesis is a statutory approach.The results showed that the form of employment contract agreement at Muse Entertainment Samarinda had implemented a work contract agreement in accordance with Article 1 paragraph (14) of Law Number 13 of 2003 concerning Manpower. Then the contents of the agreement letter contain some of the requirements listed and are in accordance with the provisions in Article 52 paragraph (1) of Law Number 13 of 2003 concerning Manpower. In the employment contract agreement, there is no stipulation on what to do when an unexpected event occurs. Muse Entertaimant Samarinda continues to carry out its obligations by providing fixed wages and benefits but no bonuses. Bonuses are non-fixed allowances in the sense that they are only given when a target is achieved. The form of protection of workers' rights that is carried out by Muse Entertainment in terms of economic protection provides employees' rights in the form of wages and fixed benefits to employees, as well as providing social welfare protection that can be said to be successful in retaining all of its employees even though in difficult situations like this, not all companies can do it. Keywords: Employment Contract, Covid-19, Night Entertainment